The Experience of philosophy - Kolak, Daniel; Martin, Raymond (New York : Oxford University Press, 2002)
A provocative and accessible anthology which focuses not on the history of philosophy but, rather, on important ideas. Although classical sources are neglected, the core of the material is recent philosophy.
Part I. beginning philosophy -- Part II. where and when -- Part III. who -- Part IV. freedom -- Part V. knowledge -- Part VI. god -- Part VII. reality -- Part VIII. experience -- Part IX. consciousness -- Part X. death -- Part XI. meaning -- Part XII. ethics -- Part XIII. values -- Epilog. concluding unphilosophical postscript.
Keywords: PHILOSOPHY